2022
DOI: 10.1108/jm2-10-2021-0251
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of modified TAM associated with e-banking services adoption: a systematic PRISMA review from 1975 to 2021

Abstract: Purpose This paper aims to review and highlight the gaps in the research streams of the technological acceptance model (TAM) associated with e-banking services. The introduction of TAM as a decision-making process from individual and organizational perspectives is the core purpose of this paper. Design/methodology/approach This study is based on concept-centric reviews and synthesizing of previous research. Data are extracted from a systematic literature review published from 1975 to 2021 under the preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…Previous theories have explained critical factors determining behavior of the customers. For example, the Theory of Reasoned Action (TRA) explain the connections between belief, attitudes, intention, and behaviors within a customer's action (Naeem et al, 2023). Meanwhile, the Theory of Planned Behavior (TPB) viewed three main components, namely, attitude, subjective norms, and perceived behavioral control that shape customers' behavioral intentions (Hosen et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous theories have explained critical factors determining behavior of the customers. For example, the Theory of Reasoned Action (TRA) explain the connections between belief, attitudes, intention, and behaviors within a customer's action (Naeem et al, 2023). Meanwhile, the Theory of Planned Behavior (TPB) viewed three main components, namely, attitude, subjective norms, and perceived behavioral control that shape customers' behavioral intentions (Hosen et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Namahoot and Laohavichien (2018), dropping the concept of social risk, showed that psychological risk is the most salient dimension of perceived risk in the behavioural intention to adopt IB. Based on a systematic literature review, Naeem et al (2022) examined the various results pertaining to the risk dimensions and identified their different applications. They argued that the perceived risk dimensions probably vary depending on the e-banking services involved.…”
Section: Theoretical Background and Hypothesis Development 21 Perceiv...mentioning
confidence: 99%
“…The factors that influence users in using information systems are perceived ease of use and perceived usefulness. Both of these factors affect the willingness of users to utilize technology (Naeem et al, 2023).…”
Section: B Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…In other words, TAM is used to explain why a technology can be applied. TAM states that the use of technology is influenced by user behavior which is influenced by perceived ease of use and perceived usefulness (Naeem et al, 2023).…”
Section: Introductionmentioning
confidence: 99%